2010
DOI: 10.1021/la904812a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Solvent Media and Temperature on the Self-Aggregation of Cationic Dimeric Surfactant 14−6−14, 2Br Studied by Conductometric and Fluorescence Techniques

Abstract: To explore how the solvent characteristics influence the self-aggregation of the cationic dimeric surfactant hexamethylene-1,6-bis(tetradecyldimethylammonium bromide) (14-6-14, 2Br(-)) and to obtain various energetic parameters, conductometric experiments were performed on the binary mixtures of three organic solvents--viz., 2-methoxyethanol (ME)-, acetonitrile (AN)-, and formamide (FA)- water (WR) at different temperatures ranging from 298.15 to 323.15 K. The steady state fluorescence measurements allowed us … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(40 citation statements)
references
References 67 publications
0
40
0
Order By: Relevance
“…4 shows the effects of octanohydroxamic acid on the aggregation number of surfactants. An increase in the content of the polar organic solvent results in decrease in N agg for cationic, anionic, non-ionic and zwitterionic surfactants [43]. The decrease of N agg was considered by the variations of thermodynamic properties viz.…”
Section: Aggregation Number (N Agg )mentioning
confidence: 99%
“…4 shows the effects of octanohydroxamic acid on the aggregation number of surfactants. An increase in the content of the polar organic solvent results in decrease in N agg for cationic, anionic, non-ionic and zwitterionic surfactants [43]. The decrease of N agg was considered by the variations of thermodynamic properties viz.…”
Section: Aggregation Number (N Agg )mentioning
confidence: 99%
“…Gordon parameter, G, gives an idea about the cohesive energy density which is related to the solubility behavior as the same intermolecular forces have to be overcome during solvation [31].…”
Section: Micellization Of Ctab In 13-butanediol/water Mixed Solventsmentioning
confidence: 99%
“…Recently, there is much interest in the properties of mixed surfactant solutions in the presence of different additives. Kolay et al [18] and Kabir-ud-Din and Koya [19] have studied the effects of organic solvents on cationic gemini surfactants and the thermodynamic properties of these surfactants. These studies showed that micellization behaviour is less favourable in (solvent + water) mixed solutions than pure water.…”
Section: Introductionmentioning
confidence: 99%